2020
DOI: 10.1051/0004-6361/202039094
|View full text |Cite
|
Sign up to set email alerts
|

Differential rotation of the solar corona: A new data-adaptive multiwavelength approach

Abstract: Context. The characterization of the differential rotation of the extended corona is still lacking conclusive results about the actual rotation rate profiles, and it is also expected to vary along the solar cycle. While some studies supported the quasi-rigidity of coronal rotation, others have found evidence of differential rotation to occur. Aims. For the purpose of investigating the differential rotation of the solar corona, we analyzed ultraviolet (UV) spectral line observations acquired on both the east an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 71 publications
(107 reference statements)
0
9
0
Order By: Relevance
“…9a and 10. This situation of a slower photosphere is particularly valid at mid to higher latitudes, typically over 30 • in latitude, as studies of the coronal hole rotation rate indicate (e.g., Giordano & Mancuso 2008;Mancuso & Giordano 2011;Bagashvili et al 2017;Mancuso et al 2020). However, analysis of the spacecraft connectivity throughout E 1 indicates that the measured solar wind observed by PSP was emerging from an equatorial coronal hole (Bale et al 2019;Badman et al 2020;Réville et al 2020), which would supposedly rotate close to the photospheric speed.…”
Section: Possible Interpretationmentioning
confidence: 98%
“…9a and 10. This situation of a slower photosphere is particularly valid at mid to higher latitudes, typically over 30 • in latitude, as studies of the coronal hole rotation rate indicate (e.g., Giordano & Mancuso 2008;Mancuso & Giordano 2011;Bagashvili et al 2017;Mancuso et al 2020). However, analysis of the spacecraft connectivity throughout E 1 indicates that the measured solar wind observed by PSP was emerging from an equatorial coronal hole (Bale et al 2019;Badman et al 2020;Réville et al 2020), which would supposedly rotate close to the photospheric speed.…”
Section: Possible Interpretationmentioning
confidence: 98%
“…During the minimum of a solar cycle, the solar disk is mainly populated by small-scale magnetic elements of Component-III 1 , 2 . Thus their finding 32 actually implies that the quiet corona should be heated mainly by the elements of Component-III during the minimum time of a solar cycle.…”
Section: The Quiet Atmospherementioning
confidence: 93%
“…Utilizing intensities of five coronal spectral lines of about 400 days during the minimum time of the solar cycle 23, Mancuso et al. 32 found that the quiet corona rotates faster than the photospheric plasma, which suggests that the quiet corona is mainly heated by small-scale magnetic structures rooted near (also in the leptocline). During the minimum of a solar cycle, the solar disk is mainly populated by small-scale magnetic elements of Component-III 1 , 2 .…”
Section: The Quiet Atmospherementioning
confidence: 99%
“…After observing power spectrum of periodogram, FAP (false alarm probability) measurement is essential to verify the probability that the dominating peak is due to any true periodic signal and is not the outcome of any noise present randomly in the time series. The FAP Assessment of a FAP level of power numerically requires at least the computation of 10/power (Chowdhury et al 2013;Delisle, Hara & Segransan 2020;Mancuso et al 2020).…”
Section: Methodsmentioning
confidence: 99%